1983
DOI: 10.1002/smj.4250040304
|View full text |Cite
|
Sign up to set email alerts
|

Strategy‐making and environment: The third link

Abstract: Whereas much is known about the relationships between strategy and structure, and between environment and structure, too little is known about a third link—the relationship between strategy‐making and environment. An empirical study was conducted upon two distinct samples of firms. We hypothesized that increases in environmental dynamism, hostility and heterogeneity should be related to specific changes in the amount of analysis and innovation which characterizes strategy‐making activity. Most of these relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,184
6
36

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,507 publications
(1,296 citation statements)
references
References 15 publications
27
1,184
6
36
Order By: Relevance
“…As key sources of environmental uncertainty, target marketplace factors could also influence an organization's ability to realize strategy in ways that accomplish desired goals (e.g., Miller & Friesen 1983;Morgan 2012). Strategic management scholars posit that an organization's environment presents uncertainty that contains both opportunities and threats, and that organizational performance is a function of the selection of goals and strategies that align with these environmental conditions (Bourgeois 1980;Qi et al 2011).…”
Section: Theory Framework Strategic Goals and Their Accomplishmentmentioning
confidence: 99%
“…As key sources of environmental uncertainty, target marketplace factors could also influence an organization's ability to realize strategy in ways that accomplish desired goals (e.g., Miller & Friesen 1983;Morgan 2012). Strategic management scholars posit that an organization's environment presents uncertainty that contains both opportunities and threats, and that organizational performance is a function of the selection of goals and strategies that align with these environmental conditions (Bourgeois 1980;Qi et al 2011).…”
Section: Theory Framework Strategic Goals and Their Accomplishmentmentioning
confidence: 99%
“…With increasing turbulence, the need for information processing increases (Tushman & Nadler, 1978), as does the level of information exchange (Daft & Lengel, 1986;Menon & Varadarajan, 1992). Dynamic environments create the need for differentiation and integration of information (Khandwalla, 1973;Miller & Friesen, 1983). Market turbulence gauges the extent that an organization perceives the composition and preferences of its customers as changing over time .…”
Section: Determinants and Consequencesmentioning
confidence: 99%
“…In fact, some have described these resource-rich industries as producing a tide that raises all boats (Wasserman et al 2001). Less munificent environments (i.e., industries with less environmental capacity) (Dess and Beard 1984), on the other hand, are characterized by intense competition (Aldrich 1979), few exploitable opportunities (Covin and Slevin 1989), and hostility (Khandwalla 1976(Khandwalla , 1977Miller and Friesen 1983). Consequently, these resource-poor industries are more "selective," and decision makers' choices have a stronger influence on performance outcomes than in more munificent industries (Covin and Slevin 1989;Tushman 1977;Zahra and Covin 1995).…”
Section: Perceived Industry Munificencementioning
confidence: 99%
“…This means that opportunities that could cause damage to the natural environment are part of a substantially smaller set of opportunities that could be pursued. Indeed, scholars have found that corporate entrepreneurship plays a more salient role in firm performance in resource-scarce industries than in industries with greater munificence (Covin and Slevin 1989;Miller and Friesen 1983;Zahra and Covin 1995). Therefore, when individuals perceive an industry as being less munificent, the importance of pursuing an opportunity that may harm the environment is likely to conflict with their pro-environmental values more than in more munificent contexts.…”
Section: Perceived Industry Munificencementioning
confidence: 99%